Alleviating an Acid Sulfate Soil Cultivated to Rice (Oryza sativa) Using Ground Magnesium Limestone and Organic Fertilizer - Totok Suswanto; J Shamshuddin; S.R Syed Omar; Peli Mat; C.B.S Teh (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
Rice yield on acid sulfate soils in Malaysia is very low, presumably due to AI and/or Fe toxicity. This study wasconducted to ameliorate an acid sulfate soil in the Kemasin-Semerak Integrated Agricultural Development Project, located in Kelantan, Peninsular Malaysia, for rice cultivation. Rice variety, MR 219, was used as the test crop. Treatment included the use of various rates of ground magnesium limestone (GML), with or without an organic fertilizer. This acid sulfate soil had an initial pH of < 3.5 at depth below 45 cm. Exchangeable AI in the soil was high, especially in the subsoil. The first crop of rice was disturbed by floods. The result for the 2